Cooperative differential games with continuous updating using Hamilton–Jacobi–Bellman equation. (2nd November 2021) - Petrosian, Ovanes; Tur, Anna; Wang, Zeyang; Gao, Hongwei
Abstract : This paper examines a class of cooperative differential games with continuous updating. Here it is assumed that at each time instant players have or use information about the game structure defined for a closed time interval with fixed duration. The current time continuously evolves with the updating interval. The main problems considered in a cooperative setting with continuous updating is how to define players' cooperative behaviour, how to construct a cooperative trajectory, how to define the characteristic function and how to arrive at a cooperative solution. This paper also addresses the properties of the solution and presents some techniques to fix the process by which a cooperative solution is constructed. Theoretical results are demonstrated on a differential game model of non-renewable resource extraction, initial and continuous updating versions are also considered. Comparison of cooperative strategies, trajectories, characteristic functions and corresponding Shapley values is presented.